The Significance of Materialism in Margayya’s Inauthenticity in R.K. Narayan’s The Financial Expert (Global Journal of Human-Social Science, 2023)
This article explores the significance of materialism in depicting the theme of inauthenticity in R K Narayan s novel The Financial Expert Focusing on the character of Margayya a financial expert driven by the pursuit of wealth the article delves into the consequences of materialistic tendencies on personal identity relationships and authenticity Through a detailed analysis of Margayya s journey this article sheds light on the complex interplay between materialism and inauthenticity offering valuable insights into the human condition and societal values
Keywords: materialism; inauthenticity; the financial expert; personal identity; relationships